A RÁDIO COMUNITÁRIA COMO VETOR DO PROCESSO DE DEMOCRATIZAÇÃO DA COMUNICAÇÃO: a experiência do Projeto Rádio Escola e as mudanças ocorridas na Rádio Z FM, em Mauá-SP - Aranha, Tais (2012)
This study deals with the democratization of communication, based on community radios. The objective is to understand how a broadcasting station can be the vector of this process, with the appropriation, by local population, of a community media, besides contributing to public policies of communication and improvement of life conditions of the local population. The theoretical frame of reference is the dialectical materialism. The research was based on literature review, as a way to establish the theoretical reference, in addition to the study of documents and semi structured interviews of participants in the School Radio Project, developed during 2010, in a partnership between the community radio Z FM and the public school Irene da Silva Costa, in Mauá City, in São Paulo State. The main conclusion is: when a community radio opens its microphones to the population in a responsible way, it allows the plural expression of ideas. Additionally, the learning about the language and the radiojournalism instruments are fostered, as well as the perception of the right of communication and the awareness of media democratization are raised.